A Study of an Agile Methodology with Scrum Approach to the Filipino Company-Sponsored I.T. Capstone Program - Ng, Giuseppe C. (International Journal of Computing Sciences Research; Vol 2 No 2 (2018): Vol 2, No 2, 2018)
Purpose – The research aims to show the relevance of company client sponsored student projects in the University of Asia and the Pacific Information Technology (UA&P IT) Capstone Program through the use ofan Agile Methodology with Scrum Approach. Method – The modified program is employed on two batches with content analysis and survey results as benchmarks. Results – Surveys at the end of the sprints for both clients and students revealed that the length of the sprint was a critical factor in the development of the information system, and that students learned from addressing additional challenges such as academic load, team pressure and communication issues. Conclusion – Over-all results showed that clients were impressed and keen to adopt the student works. Recommendations – Maintainability aspects of the research can be analyzed for future studies. Increasing the sample size with additional batches could lead to discovery of additional factors not previously seen. Research Implications – The research could help improve other Capstone Programs while improving communication with company clients.